Massive Hemoperitoneum after Paracentesis in a Patient with Budd-Chiari Syndrome: Treated with a TIPS after Negative Arteriogram - Assael, Dylan J.; Sauk, Steven C. (Seminars in Interventional Radiology, 2023)
Paracenteses are considered safe procedures; however, in patients with portal hypertension, the rapid shifts in intraabdominal pressure can prompt hemorrhage from an ectopic varix. Little literature exists on the appropriate management in this clinical setting. Here, we describe a patient with portal hypertension secondary to Budd-Chiari syndrome, presenting with massive hemoperitoneum following paracentesis. Angiography was performed, without revealing an arterial source of bleeding. Subsequently, transjugular intrahepatic portosystemic shunt placement was performed via a recanalized middle hepatic vein, reducing the patient's portosystemic gradient from 15 to 6 mm Hg. This patient developed no further signs or symptoms of bleeding and remained hemodynamically stable until discharge. Follow-up imaging confirmed patency of her shunt and resolution of her ascites, without the need for future paracentesis. This case highlights that in the absence of arterial extravasation, the possibility of ectopic variceal hemorrhage should be considered, which can be successfully treated with portosystemic shunt creation.
Keywords: paracentesis; TIPS; variceal bleed; angiography; portal hypertension